2011
DOI: 10.1007/s11103-011-9787-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of durum wheat Na+/H+ exchanger TdSOS1 by phosphorylation

Abstract: We have identified a plasma membrane Na(+)/H(+) exchanger from durum wheat, designated TdSOS1. Heterologous expression of TdSOS1 in a yeast strain lacking endogenous Na(+) efflux proteins showed complementation of the Na(+)- and Li(+)-sensitive phenotype by a mechanism involving cation efflux. Salt tolerance conferred by TdSOS1 was maximal when co-expressed with the Arabidopsis protein kinase complex SOS2/SOS3. In vitro phosphorylation of TdSOS1 with a hyperactive form of the Arabidopsis SOS2 kinase (T/DSOS2∆3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Overexpression of the truncated TdSOS1 protein in Arabidopsis showed superior tolerance to Na + and Li + stress compared with WT TdSOS1 and AtSOS1 (Feki et al, 2014). These studies on TdSOS1 show that contrary to initial reports of the function of SOS1 as a Na + /H + antiporter (Feki et al, 2011, 2014), it is now clear that at least in TdSOS1, the function also includes Li + efflux. Furthermore, Garciadeblás et al (2007) showed that SOS1 mediated low-affinity K + transport in Escherichia coli , but it failed to complement K + uptake deficiency in yeast, which leads to the question: is SOS1 involved in K + nutrition?…”
Section: Resistance To Radial Transport and Xylem Loading Of Na+mentioning
confidence: 56%
See 1 more Smart Citation
“…Overexpression of the truncated TdSOS1 protein in Arabidopsis showed superior tolerance to Na + and Li + stress compared with WT TdSOS1 and AtSOS1 (Feki et al, 2014). These studies on TdSOS1 show that contrary to initial reports of the function of SOS1 as a Na + /H + antiporter (Feki et al, 2011, 2014), it is now clear that at least in TdSOS1, the function also includes Li + efflux. Furthermore, Garciadeblás et al (2007) showed that SOS1 mediated low-affinity K + transport in Escherichia coli , but it failed to complement K + uptake deficiency in yeast, which leads to the question: is SOS1 involved in K + nutrition?…”
Section: Resistance To Radial Transport and Xylem Loading Of Na+mentioning
confidence: 56%
“…Although in the SOS pathway SOS1 is effectively involved in Na + transport, the SOS3/SOS2 or SCaBP/SOS2 complex is a determinant of its antiporter activity, implying that functional studies on SOS1 activity would require the other two components (Quintero et al, 2002) (Figure 2). However, it is now possible to circumvent this requirement, as it has been shown that deleting the C-terminal domain (auto-inhibitory and SOS2 phosphorylation site) of the Triticum durum TdSOS1 renders the protein more hyperactive than the native protein and functions in a way that is independent of SOS3/SOS2 phosphorylation (Feki et al, 2011, 2014). Overexpression of the truncated TdSOS1 protein in Arabidopsis showed superior tolerance to Na + and Li + stress compared with WT TdSOS1 and AtSOS1 (Feki et al, 2014).…”
Section: Resistance To Radial Transport and Xylem Loading Of Na+mentioning
confidence: 99%
“…Also, Thellungiella, a halophyte relative to Arabidopsis, showed higher SOS1 at both transcriptional and protein levels (Vera-Estrella et al, 2005;Kant et al, 2006;Oh et al, 2009;Taji et al, 2010). However, Feki et al (2011) showed that overexpressing TdSOS1 in Arabidopsis did not result in any significant enhancement of the salt stress tolerance in transgenic plants as compared with the performance of lines transformed with empty vectors. Is this because the wrong cell type was targeted?…”
Section: Introductionmentioning
confidence: 95%
“…However, Feki et al . () showed that overexpressing TdSOS1 in Arabidopsis did not result in any significant enhancement of the salt stress tolerance in transgenic plants as compared with the performance of lines transformed with empty vectors. Is this because the wrong cell type was targeted?…”
Section: Introductionmentioning
confidence: 98%
“…Also essential for plants is a delivery of sufficient amounts of K + to the shoot, to maintain normal cell metabolism in photosynthetically active mesophyll cells. With the application of molecular biology techniques, several candidate genes of ion transporters relevant to xylem ion loading such as Na + /H + antiporter (SOS1; Shi et al, ; Shi et al, ; Feki et al, ; Feki et al, ), high‐affinity Na + /K + ‐permeable transporter (HKT; reviewed by Horie et al, ), chloride cation co‐transporter (CCC; Colmenero‐Flores et al, ) and Shaker‐like outward channel (SKOR; Gaymard et al, ) were identified and characterized. All these transporters were found to potentially mediate xylem K + and Na + loading.…”
Section: Introductionmentioning
confidence: 99%